PENGARUH SISTEM INFORMASI AKUNTANSI, TINGKAT KEPUASAN KERJA, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN: Studi Kasus Pada KSP Kopdit Obor Mas Cabang Ende - Hardiyanti, Andi; Kapa, Sesilianus; Ismail, Nuraini (Program Studi Akuntansi Universitas Flores, 2021)
This study aims to determine the effect of accounting information systems, level of job satisfaction, organizational culture, and work discipline on employee performance at KSP Kopdit Obor Mas Branch Ende. The data collection method used a questionnaire distributed to employees. The questionnaires that were divided were 33 and were filled out completely and can be processed. The data is processed using the SPSS program. The data analysis technique used was multiple linear regression analysis. The results of this study indicate (1) The accounting information system has a significant effect on employee performance, the regression coefficient value is 0.369 with a value of tcount > ttable (3.401 > 1.70113) a significant level of 0.002 <0.05. (2) The level of job satisfaction has a significant effect on employee performance, the regression coefficient value is 0.243 with a value of tcount > ttable (2.686 > 1.70113) a significant level of 0.008 <0.05. (3) Organizational culture has a significant effect on employee performance, the regression coefficient value is 0.436 with a value of tcount > ttable (5.784 > 1.70113) with a significant level of 0.000 <0.05. (4) Work discipline has a significant effect on employee performance, the regression coefficient value of the Work Discipline variable is 0.185 with a value of tcount > ttable (2,969 > 1.70113) and a significant level of 0.012 < 0.05.